The Effect of Emotional Intelligence and Leadership Style on Employee Performance at Al-Syukro Universal Islamic College, South Tangerang - Ellya, Fariza; Sunarsi, Denok (STEBIS Bina Mandiri, 2025)
The purpose of this study was to determine the effect of emotional intelligence and leadership style on employee performance at Al-Syukro Universal Islamic College, South Tangerang. The method used was quantitative. The sampling technique used saturated sampling, namely 80 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are emotional intelligence has a significant effect on employee performance with a determination coefficient value of 51.7% and the hypothesis test obtained t count> t table or (9.135> 1.991). Leadership style has a significant effect on employee performance with a determination coefficient value of 40.5% and the hypothesis test obtained t count> t table or (7.293> 1.991). Emotional intelligence and leadership style simultaneously have a significant effect on employee performance with a regression equation Y = 9.270 + 0.471X1 + 0.290X2. The coefficient of determination is 57.2%, while the remaining 42.8% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (51.458 > 2.720).